2007
DOI: 10.1002/aic.11148
|View full text |Cite
|
Sign up to set email alerts
|

Axial mass transfer in Taylor flow through circular microchannels

Abstract: in Wiley InterScience (www.interscience.wiley.com).A Computational Fluid Dynamics (CFD) model has been formulated to evaluate axial mixing in Taylor flow. The residence-time distribution (RTD) curves of a Taylor flow unit cell (comprised of a liquid slug and two half bubbles) is calculated numerically from a step-tracer simulation by solving the steady-state Navier-Stokes and the transient convection-diffusion equations for a variety of conditions (10 < Pe < 10 5 , 10 À5 < Ca < 10 À3 ). The concentration calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Higher flow rates of continuous phase also imply a relatively thicker film thereby yielding greater extent of back mixing. Similar observations are also reported by Salman et al 25 on the basis of CFD simulations segmented flow. The effect of slug/drop sizes on dispersion 25 and on mixing in the drops 15 has been studied numerically and is known to be significant.…”
Section: Measurementssupporting
confidence: 90%
See 1 more Smart Citation
“…Higher flow rates of continuous phase also imply a relatively thicker film thereby yielding greater extent of back mixing. Similar observations are also reported by Salman et al 25 on the basis of CFD simulations segmented flow. The effect of slug/drop sizes on dispersion 25 and on mixing in the drops 15 has been studied numerically and is known to be significant.…”
Section: Measurementssupporting
confidence: 90%
“…23 Based on an early experimental analysis, Thulasidas et al 24 have reported a two-zone model where the film region and the bulk region of a liquid slug were modeled differently to take into account the mass transfer of tracer between these two zones. This approach was further extended by Salman et al 25 for understanding the effect of interslug mass transfer on axial dispersion in segmented flow. Their observations indicate that typical plug flow nature was observed at high Pe while a long tail was observed at low Pe and these observations were independent of Re.…”
Section: Introductionmentioning
confidence: 99%
“…More recently they developed a computational fluid dynamics model for the axial dispersion and residence time distribution in a straight two-dimensional gassegmented channel flow. 25 Muradoglu et al 26 studied the axial dispersion in the gas-segmented flow using a finitevolume/front-tracking ͑FV/FT͒ method and examined the effects of the Peclet number, capillary number, and segment size in a straight two-dimensional channel. Kreutzer et al 27 studied the axial dispersion in a straight rectangular microchannel and found that the liquid-filled menisci significantly increase the leakage and the axial dispersion is the least when the liquid flow rate is greater than the gas flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…The elongated bubble has a characteristic capsular shape with an equivalent diameter larger than the channel width, and the bubble itself is separated from the channel wall by a very thin liquid film. Salman et al 35 had carried out the numerical study on the axial mixing in Taylor flow through circular microchannels. It was found that increasing film thickness resulted in larger and more distinct peaks in the unit cell residence-time distribution (RTD) curve, and the separation between the peaks increased while their size decreased with an increase in the length of the liquid slug.…”
Section: Introductionmentioning
confidence: 99%